University Staffs' Everyday Engagement with Digital Technology - Exploring the Role of Information Literacy and Digital Literacy - Milla Aavakare; Shahrokh Nikou (International Telecommunications Society (ITS), 2020)
Educational environments, such as universities, have been deeply affected by technologically driven change. In fact, educational technologies are becoming progressively common, and scholars have stated that there is an expectation for these technologies to be a part of formal learning environments. Hence, university staff are expected to use digital technologies in their work activities. These expectations, however, rely on university staff's capabilities to use such technologies, thus highlighting the importance of literacy skills. This paper aims to explore the impact of information literacy (IL) and digital literacy (DL) on university staff's intention to use digital technologies in their work activities. To support this aim, a conceptual model is composed of constructs such as performance expectancy, effort expectancy and habit from the UTAUT2 framework, while incorporating the dimensions of information literacy and digital literacy. The conceptual model is then assessed with data obtained from 100 university employees thorough partial least squares structural equation modelling (PLS-SEM). The results indicate there is a direct and significant relationship between information literacy and intention to use digital technologies, whereas the relationship between digital literacy and intention to use is mediated through performance expectancy and habit. Furthermore, performance expectancy and habit possess a direct impact on intention to use technology.
Keywords: 330; Digitalisation; digital literacy; digital tools; higher education institutions; information literacy; university staff; UTAUT; UTAUT2